Big Data in the Public Sector: A Systematic Literature Review - Fredriksson, Cecilia; Mubarak, Farooq; Tuohimaa, Marja; Zhan, Ming (Scandinavian Journal of Public Administration, 2017)
This systematic literature review describes how the concept of Big Data in the public sector is understood theoretically and practically in the academic field. The article’s aim is to achieve a comprehensive understanding of Big Data in the public sector, an un- derstanding which does not currently exist. In order to ensure an accurate investigation in accordance with the inclusion criteria, 156 items of literature were selected from 1,643 articles and publications. Five themes were selected in order to obtain more knowledge about the topic; evolution, definition, applications, challenges and the future of Big Data in the public sector. Our findings show that such themes have been emerging more widely since 2012, however, a definition of Big Data has still not been agreed. Big Data is most commonly described with reference to its characteristics. Practical applications related to Big Data in the public sector were consequently studied, as were the challenges and pot- ential challenges that are emerging in the management of Big Data. There is great pot- ential for public administration organisations to benefit from Big Data in the future, both from its practical operations as well as its strategic management in the public sector do- main.